Echinocystic Acid Inhibits Inflammation and Exerts Neuroprotective Effects in MPTP-Induced Parkinson’s Disease Model Mice - He, Dewei; Hu, Guiqiu; Zhou, Ang; Liu, Yanting; Huang, Bingxu; Su, Yingchun; Wang, Hefei; Ye, Bojian; He, Yuan; Gao, Xiyu; Fu, Shoupeng; Liu, Dianfeng (Frontiers in Pharmacology, 2022)
Parkinson's disease (PD) is the second primary neurodegenerative disease affecting human health. It is mainly characterized by dopaminergic neurons damage in the midbrain and the clinical manifestation of movement disorders. Neuroinflammation is one of the causes of PD. Echinocystic acid (EA) exhibits an anti-inflammatory effect in peripheral tissues. However, whether it exerts an anti-neuroinflammation effect remains unclear. Therefore, the current study investigates the effect of EA on neuroinflammation and whether it can improve PD symptoms through anti-neuroinflammation. In our experiments, we discovered that EA inhibited pro-inflammatory mediator production in LPS-exposed BV2 cells. Further mechanism-related studies revealed that EA inhibited inflammation by activating PI3K/Akt and inhibiting NF-κB and MAPK signaling pathways in LPS-induced BV2 cells. Research revealed that EA eases microglia-mediated neuron death in SN4741 and SHSY5Y cells. In vivo studies, the results demonstrated that EA improves weight loss and behavioral impairment in MPTP-induced mice. Further studies have revealed that EA inhibited dopaminergic neurons damage and inflammation in mice midbrain. In conclusion, our study demonstrated that EA inhibits neuroinflammation and exerts neuroprotective effects by activating PI3K/Akt and inhibiting NF-κB and MAPK signaling pathways in vivo and in vitro.